2021
DOI: 10.1371/journal.pone.0255094
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural disparities in institutional delivery among women in East Africa: A decomposition analysis

Abstract: Background Though institutional delivery plays a significant role in maternal and child health, there is substantial evidence that the majority of rural women have lower health facility delivery than urban women. So, identifying the drivers of these disparities will help policy-makers and programmers with the reduction of maternal and child death. Methods The study used the data on a nationwide representative sample from the most recent rounds of the Demographic and Health Survey (DHS) of four East African c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(59 reference statements)
1
10
1
1
Order By: Relevance
“…Besides women who live in rural areas have shown a lower risk of encountering delays two and three compared with their counterparts who live in urban areas. The finding was comparable with studies done elsewhere [24,[82][83][84], which revealed the presence of inequality in maternal service utilization based on residence and region. The likely explanation for this could be the fact that women who reside in rural areas and pastoralist regions have limited information on maternity services; in addition, this could also be due to the challenge residents face in accessing health facilities within a reasonable distance and time.…”
Section: Plos Onesupporting
confidence: 89%
“…Besides women who live in rural areas have shown a lower risk of encountering delays two and three compared with their counterparts who live in urban areas. The finding was comparable with studies done elsewhere [24,[82][83][84], which revealed the presence of inequality in maternal service utilization based on residence and region. The likely explanation for this could be the fact that women who reside in rural areas and pastoralist regions have limited information on maternity services; in addition, this could also be due to the challenge residents face in accessing health facilities within a reasonable distance and time.…”
Section: Plos Onesupporting
confidence: 89%
“…More importantly, delivering at home could delay life-saving treatment should complications due to childbirth occur. 8 Compared to similar studies in the African region, 28 30 we found wealth index had the most pronounced effect on both urban and rural estimates although there is consistency in the finding that more rural women deliver at home. This may be driven by income differences with use of maternal and child health services favoring the rich despite subsidies.…”
Section: Discussioncontrasting
confidence: 64%
“…Urban-rural estimates on place of delivery have been published using data from the African region and have shown that there are notable differences in the uptake of skilled delivery services in urban and rural communities. [28][29][30] Such studies are especially important with the ongoing COVID-19 pandemic overwhelming the health system and further discouraging women to seek health care and services in health facilities. Because women are often disproportionately affected during disasters, further strengthening the health facilities across the country and integrating in the pandemic response strategies for women to birth safely will be critical to advancing progress to reduce maternal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to COVID-19, urban-rural disparities in access to SRH services in Ethiopia were well-documented [ 39 , 40 ]. We found that geographic barriers to access became more pronounced during the pandemic, particularly due to limited and costly transportation options, and inequities in availability of both COVID-19 and SRH services.…”
Section: Discussionmentioning
confidence: 99%